CONTRIBUTIONS OF MOTHER TONGUE EDUCATION IN EARLY CHILDHOOD EDUCATION - Babajide Gboyega, Abidogun; Oluranti Idiat, Adebule (European Scientific Journal, ESJ, 2014)
Early Childhood Education is very essential in a child’s life hence the recent focus on it across the globe. It is that education that provides for children whose age bracket is from 0 to 8 years. To demonstrate the significance of Mother Tongue education in Early childhood development, February 21-22 of every year is set aside as the International Mother Tongue Day globally. The declaration by UNESCO in 1999 further emphasized the relationship between the two concepts. This paper examines the contributions of Mother Tongue Education in Early Childhood. Issues raised will be discussed under the following six subdivisions: background of language situation in Nigeria; policy document on language in Nigeria; language theories and development; problem statement and rationale; success and failures of MT in countries and suggestions on the way forward.